The effect of Saliva officinalis extract on the menopausal symptoms in postmenopausal women: An RCT - Fereshteh Dadfar; Kourosh Bamdad (Shahid Sadoughi University of Medical Sciences, 2019)
Background The menopausal symptoms are the most common problems in postmenopausal women. Due to the side effects of hormone replacement therapy, the use of medicinal herbs has increased for the treatment of menopausal symptoms. Objective The aim of this study was to evaluate the effect of Saliva officinalis on the decreasing of the severity of the menopausal symptoms in postmenopausal women. Materials and Methods The study was performed on 30 postmenopausal women aged 46-58 yr referred to the healthcare center of Darab who experienced various degrees of postmenopausal symptoms. The severity of menopausal symptoms is recorded by a Menopause Rating Scale. Participants received a 100 mg capsule of sage extract daily for 4 wk. The severity of postmenopausal symptoms was compared before and after four weeks of the consumption of sage extract. Results The results showed the severity of hot flashes, night sweats, panic, fatigue, and concentration had significant differences before and after the consumption of sage extract. Conclusion It was concluded that Saliva officinalis were effective to change the severity of some of the menopausal symptoms in postmenopausal women.